Beberapa Faktor yang Mempengaruhi Fertilitas di Desa Sumberagung, Kecamatan Wates, Kabupaten Kediri - Nur Anggraeni Agustina Wati; Budijanto Budijanto; M. Yusuf Idris (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2025)
Fertility is a tangible result of the reproduction of a person or a group of women concerning the number of children born alive. One calculation for determining fertility in general is crude birth rate, crude birth rate is the number of live births in an area every 1.000 population at midyear. Eligible couples in Sumberagung Village as much as 1.476 inhabitants is still lower when compared with the village of Tawang and Duwet village, but it has the highest number of births. CBR Sumberagung village reached 11,72 and amounted to 7,81 so that CDR in the number of inhabitants amounted to 3,91. This reserach uses a study design parameters with the correlational approach and survey method. Sampling is done proportionally random sampling with respondents who ever married women amounted to 90 people. The dependent variable in this study is fertility, while the independent variables are age at first marriage, length of reproductive period, length of contraceptive use, infant mortality, education level, and income. The results of multiple linear regression analysis shows that together independent variables affect the dependent variable fertility. Partially age at first marriage, long reproductive period, duration of use of contraception, and education level affect the fertility while infant mortality and income level had no effect on fertility. The most dominant variable influence on fertility is a long period of reproduction and the smallest contribution is income level.